Dansyl Based “Turn-On” Fluorescent Sensor for Cu2+Ion Detection and the Application to Living Cell Imaging - Weerachai Nasomphan (2018)
© 2017, Springer Science+Business Media, LLC. A new “turn-on” fluorescent chemosensor based on dansyl derivative was prepared for Cu2+ion sensing. Hydroxyl, imine and azomethine groups in Schiff base derived compound 1 were deliberately introduced for facilitating the binding of Cu2+ion. Of screen metal ions, compound 1 showed a high degree of selectivity toward Cu2+ion. Other interfering metal ions did not affect the fluorescence intensity of compound 1, except Hg2+and Fe3+ions exhibited a significant degree of fluorescence quenching. Upon binding of Cu2+ion, compound 1 displayed a chelation enhanced fluorescence (CHEF) resulting in increasing of the fluorescence intensity. The molecular optimized geometry indicated the binding ratio between compound 1 and Cu2+ion at 1:1 with the binding constant of 1.68 × 10− 7M− 1. The optimized condition for sensing ability of compound 1 with a detection limit of 5 × 10− 7M was found at the physiological pH 7.2 with the excitation wavelength of 366 nm. Due to no cytotoxicity and good photophysical properties, compound 1 was extended its application for the detection of Cu2+ion in Vero cells. Compound 1 could be potentially used as an intracellular fluorescent chemosensor for tracking Cu2+ion. [Figure not available: see fulltext.].